Electrospray Nested Energetic Cells from Nanothermite with MoO3 Nanostrips: Reactivity, Sensitivity and Combustion Performance - Yaru Li; Hui Ren; Quanmin Xie (Applied Sciences, 2024)
Nanothermites have attracted great attention over the last two decades for their superior performance in heat release and pressure wave generation. The shape of the oxidizer and the assembly structure could significantly influence the performance. This paper reports on the reactivity, sensitivity and combustion performance of nanothermite of aluminum nanoparticles and MoO3 nanostrips prepared via electrospray strategy. The resulting particles were in good integrity, resembling bird nests. There were two exothermic processes for the resulting composites, which successively conformed to the Avrami–Erofeev equation of n = 4 and the Zhuravlev–Lesokhin–Tempelman (Z-L-T) equation. And the corresponding activation energies for the two processes were 148.645 kJ/mol and 297.280 kJ/mol, respectively. The flame sensitivity and impact sensitivity for the electrosprayed product were 50 cm and 35 cm, respectively, which were both higher than those of the mechanically mixed counterpart. The constant-volume combustion test showed that the maximum pressure of the electrosprayed product was 1.96 MPa, which was 0.69 MPa higher than that of the mechanically mixed counterpart. The combustion performances were evaluated under confined and unconfined conditions. Due to the fast heat release and transfer efficiency, fierce deflagration was achieved in the case of the electrosprayed sample under confined conditions. The combustion rate of the electrosprayed sample under unconfined conditions was almost a hundred times as much as that of the mechanically mixed one.